Deciphering transcriptome patterns in porcine mesenchymal stem cells promoting phenotypic maintenance and differentiation by key driver genes - Nadia Khaveh; Nadia Khaveh; René Buschow; Julia Metzger; Julia Metzger (Frontiers in Cell and Developmental Biology)
Mesenchymal stem cells (MSC) are fibroblast-like non-hematopoietic cells with self-renewal and differentiation capacity, and thereby great potential in regeneration and wound healing. MSC populations are heterogeneous not only inherently, but also among different model species. In particular, porcine MSC serve as a frequently used resource for translational research, due to pigs’ distinctive closeness to human anatomy and physiology. However, information on gene expression profiles from porcine MSC and its dynamics during differentiation is sparse, especially with regard to cell surface and inner cell markers. In this study, we investigated the transcriptome of bone marrow-derived MSC and its differentiated cell types in a minipig breed for experimental research, known as Mini-LEWE, using bulk mRNA sequencing. Our data highlighted Rap1 signaling and downstream pathways PI3K-Akt and MAPK signaling as potential players for the maintenance of stemness of BM-MSC. In addition, we were able to link the process of differentiation to changes in the regulation of actin cytoskeleton. A total of 18 “BM-MSC differentiation driver markers” were identified, potentially promoting the process of differentiation into adipocytes, chondrocytes as well as osteocytes. Our results offer a new perspective on the molecular phenotype of porcine BM-MSC and the transcriptional responses in new differentiated progeny.